Microanatomy of the central myelin-peripheral myelin transition zone of the trigeminal nerve - (:unkn) unknown (OXFORD UNIV PRESS INC, 2006)
OBJECTIVE: The aim of this study was to evaluate the microanatomy of the central myelin-peripheral myelin transitional zone (TZ) in trigeminal nerves from cadavers. METHODS: One hundred trigeminal nerves from 50 cadaver heads were examined. The cisternal portion of the nerve (from the pons to Meckel's cave) was measured. Horizontal sections were stained and photographed. The photomicrographs were used to measure the extent of central myelin on the medial and lateral aspects of the nerve and to classify TZ shapes. RESULTS: The cisternal portions of the specimens ranged from 8 to 15 mm long (mean, 12.3 mm; median, 11.9 mm). The data from the photomicrographs revealed that the extent of central myelin (distance from pons to TZ) on the medial aspect of the nerve (range, 0.1-2.5 mm; mean, 1.13 mm; median, 1 mm) was shorter than that on the lateral aspect (range, 0.17-6.75 mm; mean, 2.47 mm; median, 2.12 mm). CONCLUSION: The data definitively prove that the root entry zone (REZ, nerve-pons junction) and TZ of the trigeminal nerve are distinct sites and that these terms should never be used interchangeably. The measurements showed that the central myelin occupies only the initial one-fourth of the trigeminal nerve length. If trigeminal neuralgia is caused exclusively by vascular compression of the central myelin, the problem vessel would always have to be located in this region. However, it is well known that pain from trigeminal neuralgia can resolve after vascular decompression at more distal sites. This suggests that the effects of surgical decompression are caused by another mechanism.
Keywords: anatomy; microvascular decompression; trigeminal nerve; trigeminal neuralgia; MICROVASCULAR DECOMPRESSION; CRANIAL NERVES; NEURALGIA; COMPRESSION; ROOT; PATHOPHYSIOLOGY; MANAGEMENT; PAIN